(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Carburizing temperature plays an important role for carbon to disperse deep inside the steel surface. Pack carburizing requires higher temperatures to disperse the carbon compared to gas carburizing and bed carburizing. Introduction of different carburizing media (powder and paste compound) might contribute toward the effectiveness of this process. This paper investigates on the effect of different temperature (700oC-1000oC) using powder and paste compound towards the carbon dispersion in carburized steel. Mild steel was used as the substrate material which has been carburized using the powder and paste compound with a ratio of 1:1 and 3:1,respectively. The temperatures has been set at 700oC, 800oC, 900oC and 1000oC for 8 hours. The effects of carbon dispersion layers were observed by the increasing depth of case hardness. The chemical composition analysis was done by using a spectrometer to see the increment of carbon content of the carburized steel. Results showed that the paste compound at a temperature of 1000oC significantly influenced the hardness properties and carbon composition as compared to the carburized steel obtained from the powder compound.